Developing the Creativity of Elementary School Students in Cimahi, Indonesia Through Online Learning Media During the COVID-19 Pandemic - Ariyanti, Nuraini Dwi S.; Maryanti, Rina (Indonesian Journal of Teaching in Science, 2022)
The impact of the COVID-19 pandemic can be felt in several sectors in Indonesia, especially in the education sector. In the education sector, this is certainly very influential on student learning going online. This online learning activity sometimes students feel more bored and bored so that students find it difficult to understand the material that has been given by the teacher. To be able to overcome such things, it is necessary to make online learning that involves students' creativity. The purpose of this study was to develop the creativity of Purnama Elementary School students in Cimahi City through online learning media during the Covid-19 pandemic. By using a descriptive qualitative approach and research techniques with interviews with the principal and teachers of SD Purnama, it is stated that there are still 3rd-grade students at SD Purnama who are less creative in carrying out assignments and are less enthusiastic in online learning. The results of this study stated that there were still many students who were less creative and lacked enthusiasm in doing assignments and also in this online learning. Because during the KKN there they saw that there was indeed a student who did simple tasks, such as drawing carelessly. This research hopes that online learning activities can increase students' creativity.